Mapping Global Research Trends on Smart Farming Using Bibliometric Analysis 2010–2025 - Loso Judijanto (West Science Agro, 2026)
This study maps global research trends on smart farming through a bibliometric analysis of Scopus-indexed publications published between 2010 and 2025. Using VOSviewer as the primary analytical tool, the study examines publication growth, co-authorship networks, institutional and country collaborations, keyword co-occurrence structures, overlay visualization, and thematic density patterns. The results indicate a significant increase in scholarly output over the study period, reflecting the rapid expansion of digital and intelligent technologies in agriculture. India emerges as a central hub in international collaboration networks, while technology-oriented universities and computer science departments play a dominant role in knowledge production. The keyword analysis reveals that smart agriculture and precision agriculture form the intellectual core of the field, strongly connected to Internet of Things, machine learning, deep learning, remote sensing, and agricultural machinery. Overlay visualization demonstrates a temporal shift from infrastructure-focused research toward AI-driven analytics and sustainability-oriented applications, particularly in relation to climate change and food security. The study highlights the transition of smart farming research toward an integrated Agriculture 4.0 paradigm and identifies future directions related to interoperability, data governance, inclusive adoption, and measurable sustainability impacts.